Comparison of Ahmed Versus Baerveldt Implant Outcomes in Malayan Glaucoma Patients - Artini, Widya; Mustafa, Syukri; Octariana, Virna D; Suryono, Astrianda (UI Scholars Hub, 2018)
Background: Ahmed and Baerveldt implants have already have been established for treating refractory glaucoma, but, to date, their outcome in Malayan eyes has not yet been reported. This study aimed to evaluate a comparison of the success rate between Ahmed and Baerveldt implants surgical intervention in Malayan patients with glaucoma. Methods: A descriptive retrospective study was conducted at Cipto Mangunkusumo Hospital, Indonesia, from January 2013 to December 2015. All glaucoma patients who underwent Ahmed and Baerveldt implants and intraocular pressure (IOP), and presented for follow-up evaluation one year post implant, were enrolled in this study. Visual acuity and complications were also recorded. A comparison between the two groups was then analysed. Results: The study cohort included a total of 117 eyes, of which 64 and 53 received the Ahmed and Baerveldt implants, respectively. The pre-operation IOP between the two groups was found to be significantly different (p = 0.01), but no significant difference (p = 0.24) was observed after surgery, although both groups showed a declining IOP. Complete success was achieved in 75% of Ahmed and 60.38% of Baerveldt implant patients. Overall, 9 patients developed complications. Conclusions: Both the Ahmed and Baerveldt implant groups demonstrated similar success in reducing IOP.